Reproductive Outcomes in Women with Prior Cesarean Section Undergoing In Vitro Fertilization：A Retrospective Case-control Study - 王雅琴;尹太郎;徐望明;漆倩荣;王笑臣;杨菁 (Current medical science, 2017)
The impact of prior cesarean section（CS） on the pregnancy and neonatal outcomes of in vitro fertilization and embryo transfer（IVF-ET） was investigated. A retrospective analysis was performed on 144 patients with prior CS between January 2013 and December 2015. The pregnancy, delivery, and neonatal outcomes of patients who had previous CS delivery and received IVF-ET were analyzed. The control group comprised 166 patients who had only previous vaginal delivery（VD） and received IVF-ET during the same period. The results showed that the basal follicle stimulating hormone level, estradiol level on human chorionic gonadotropin（h CG） day, gonadotrophin dosage, duration of stimulation, retrieved oocytes, fertilization rate, high-quality embryo rate, multiple birth rate, abortion rate and ectopic pregnancy rate had no significant difference between the two groups（P〉0.05）. The pregnancy rate（40.28% vs. 54.22%） and implantation rate（24.01% vs. 34.67%） were significantly lower（P〈0.05）, and the ratio of embryo difficulty transfer（9/144 vs. 0/166） was significantly higher in CS group than in VD group. The risk of pernicious placenta previa and postpartum hemorrhage in twin deliveries was significantly increased in CS group as compared with that in VD group（P〈0.05）, and gestational age and neonatal birth weight were significantly reduced in twin deliveries as compared with singleton deliveries in both groups（P〈0.05）. It was suggested that the existence of CS scar may impact embryo implantation and clinical pregnancy outcome, and increase the difficulty of ET. We should limit the number of transfer embryos to avoid multiple pregnancies and strengthen gestational supervision in patients with cesarean scar.